2017
DOI: 10.1080/21568235.2017.1373027
|View full text |Cite
|
Sign up to set email alerts
|

‘It doesn’t really matter which university you attend or which subject you study while abroad.’ the massification of student mobility programmes and its implications for equality in higher education

Abstract: It doesn't really matter which university you attend or which subject you study while abroad." The Massification of Student Mobility Programmes and its Implications for Equality in Irish Higher Education.Based on documentary analysis and interviews, the article examines the current practices of Irish universities in their efforts to increase their students' participation in international exchange programmes. It argues that increased participation, while a positive outcome, obscures a growing differentiation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 30 publications
0
19
0
1
Order By: Relevance
“…A significant body of research has questioned some of the assumptions around the 'massification' of mobility and its benefits. Courtois (2018) critiques the institutional strategies of promoting mobility since the effect can be reinforcing existing social structures and privileges; a point which has also been made in other works on the phenomenon (Gerhards and Hans 2013;Netz and Finger 2016).…”
Section: Study Abroad and Academic Successmentioning
confidence: 89%
See 1 more Smart Citation
“…A significant body of research has questioned some of the assumptions around the 'massification' of mobility and its benefits. Courtois (2018) critiques the institutional strategies of promoting mobility since the effect can be reinforcing existing social structures and privileges; a point which has also been made in other works on the phenomenon (Gerhards and Hans 2013;Netz and Finger 2016).…”
Section: Study Abroad and Academic Successmentioning
confidence: 89%
“…Students who have weaker grades are encouraged to apply as much as those with higher grades and there are multiple points of contact within the School/University to discuss issues of concern (such as health conditions, disabilities, lack of confidence or limited financial resources) to ensure appropriate additional help. The latter mitigates against some of the downsides to 'massification' of exchanges as identified by Courtois (2018) and the risk of reinforcing social inequalities (Marginson (2016)).…”
Section: Sample Selectionmentioning
confidence: 99%
“…Evidently then, quality is not necessarily only about what students learn academically or professionally when going abroad but can be achieved through the mobility experience itself. In the interplay with a bureaucratic understanding of mobility, it is suggested that there are indeed factors leading to what could be called a mobility drift-a promotion of mobility for the sake of mobility, as also found in other studies (Castro et al, 2016;Courtois, 2018;Teichler, 2017). Yet, the present study suggests that actors contribute somewhat to this instrumentalisation by promoting an idea according to which all or most mobility is good mobility, as long as teacher students, who are perceived as less inclined to engage in mobility, actually go abroad.…”
Section: Discussion and Con Clus I On Smentioning
confidence: 56%
“…To this date, the drivers and effects of short-term mobility have largely been explored from overall policy approaches (e.g., Dvir & Yemini, 2017;Rivza & Teichler, 2007), or student-centred approaches (e.g., Beerkens et al, 2015;van Mol, 2014). Such perspectives tend to obscure the institutions and actors who also play an important role in processes of student mobility (Brooks, 2018;Courtois, 2018). From this starting point, a range of scholarly contributions on what characterises mobility and how its translation into practice may be shaped by actors and contexts form the backdrop for the analysis and discussion pursued in this article.…”
Section: G Round -Le Vel Ac Tor S' Per S Pec Tive S On S Tudent Mob Ilit Ymentioning
confidence: 99%
“…al., 2018) Sin embargo, algunas instituciones de educación superior y sus respectivos programas se diferencian cada vez más manteniendo la selectividad y el prestigio, mientras que otras de menor prestigio son las que reciben un alto número de estudiantes provenientes de familias de clases trabajadoras, que pertenecen a la primera generación de sus familias que acceden a la educación superior. Por lo tanto, esta mayor participación que es percibida como un resultado positivo, oculta una creciente diferenciación en los tipos de programas e instituciones, provocando una progresiva estratificación en el sistema (Courtois, 2018). De este modo, por ejemplo, en Alemania las instituciones universitarias que han expandido su matrícula recientemente se identifican de manera uniforme por representar la más alta educación y mantener así el carácter elitista de su expansión (Stock, 2018).…”
Section: Estudiantes De Primera Generación Y…unclassified